Assessment of Serum Alpha-Fetoprotein, Triphasic CT, and Renal Parameters in the Early Detection of Hepatocellular Carcinoma - Aysha Abdul Rauf Nazir Ahmed, Ali Saqlain Haider, Muhammad Hamza Bajwa, Muhammad Adnan Sadiq, Sumera Saghir, Irfana Hassan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Early detection of hepatocellular carcinoma (HCC) remains critical to enable curative therapies and improve survival. The present case-control study evaluates three modalities—serum alphafetoprotein (AFP), triphasic computed tomography (CT) imaging, and selected renal parameters (serum creatinine, estimated glomerular filtration rate [eGFR], and albuminuria)—for their utility in identifying early-stage HCC among high-risk patients with chronic liver disease.